2019
DOI: 10.1111/jpn.13114
|View full text |Cite
|
Sign up to set email alerts
|

The effect of astragaloside IV on JAK2‐STAT6 signalling pathway in mouse model of ovalbumin‐induced asthma

Abstract: Asthma is a chronic inflammatory lung disease of the airway; the incidence and prevalence of asthma remain high worldwide. Astragaloside IV (AS‐IV) is the main active constituent of Astragalus membranaceus. Accumulating evidence suggests that AS‐IV possesses anti‐inflammatory and anti‐asthmatic ability, but the potential molecular mechanism is required to further clarify. In this study, the anti‐asthmatic effects of AS‐IV on mice with ovalbumin (OVA)‐induced allergic inflammation were analysed. We analysed air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that AS-IV has pharmacological effects as an anti-oxidant, anti-inflammatory, immunomodulatory, antiviral, and antitumor agent. 27 In recent years, AS-IV has received attention in the prevention of respiratory diseases, such as asthma, 28 pulmonary fibrosis 29 and lung cancer. 30 However, there are few reports on the prevention of PM2.5-induced lung injury by AS-IV through modulation of the autophagic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that AS-IV has pharmacological effects as an anti-oxidant, anti-inflammatory, immunomodulatory, antiviral, and antitumor agent. 27 In recent years, AS-IV has received attention in the prevention of respiratory diseases, such as asthma, 28 pulmonary fibrosis 29 and lung cancer. 30 However, there are few reports on the prevention of PM2.5-induced lung injury by AS-IV through modulation of the autophagic pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, JAK2 controls white blood cells, a number of red blood cells and platelets that are correlated with severe asthma. Recent clinical validations indicate that inhibition of the JAK2/STAT6 signaling pathway may be considered for ovalbumin-induced asthma therapies [26]. Thus could confirm the strong association of JAK2, STAT3 and severe asthma.…”
Section: Discussionmentioning
confidence: 88%
“…Many studies have demonstrated that AS-IV can protect the cardiovascular system, lungs, kidneys and brain, an effect attributed to its anti-inflammatory, antioxidant, anti-apoptotic and immunoregulation properties ( Yan et al, 2017 ; Meiqian et al, 2018 ; Zhang et al, 2019 ; Tan et al, 2020 ). It has been shown that AS-IV could counter inflammation through multiple signaling pathways, such as Toll like receptor four/nuclear factor–kappa B (TLR4/NF-κB) signaling pathway, mitogen-activated protein kinases (MAPK) signaling pathway, and Janus kinase two/signal transducer and activator of transcription 6 (JAK2/STAT6) signaling pathway ( Leng et al, 2019 ; Yang and Wang, 2019 ; Hsieh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%